2018
DOI: 10.1016/j.jocn.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and positron emission tomography in anti-NMDA receptor encephalitis: A systematic review

Abstract: Due to a variety of clinical manifestations anti-N-methyl-d-aspartate (NMDA) receptor encephalitis may be difficult to diagnose. Magnetic resonance imaging (MRI) may be used as a component of the workup for encephalopathy. However, the use of MRI in anti-NMDA encephalitis is complicated by wide-ranging reports regarding the frequency of normal MRI findings in this disease. Positron emission tomography (PET) is a modality of imaging that may assess functional rather than structural disturbances. Therefore, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 57 publications
6
107
0
4
Order By: Relevance
“…Even higher rates of this pattern have been observed in children, and non‐specific EEG abnormalities, such as diffuse slowing, are common . Neuroimaging is rarely helpful in making an early diagnosis of anti‐NMDArE, although magnetic resonance imaging may be abnormal in more than half of patients within 3 months of illness onset, and a magnetic resonance imaging measure of large‐scale brain network connectivity shows promise as a diagnostic tool …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even higher rates of this pattern have been observed in children, and non‐specific EEG abnormalities, such as diffuse slowing, are common . Neuroimaging is rarely helpful in making an early diagnosis of anti‐NMDArE, although magnetic resonance imaging may be abnormal in more than half of patients within 3 months of illness onset, and a magnetic resonance imaging measure of large‐scale brain network connectivity shows promise as a diagnostic tool …”
Section: Discussionmentioning
confidence: 99%
“…10,18,31 Even higher rates of this pattern have been observed in children, [32][33][34] and non-specific EEG abnormalities, such as diffuse slowing, are common. 31,32 Neuroimaging is rarely helpful in making an early diagnosis of anti-NMDArE, 22,24,35 although magnetic resonance imaging may be abnormal in more than half of patients within 3 months of illness onset, 14 and a magnetic resonance imaging measure of large-scale brain network connectivity shows promise as a diagnostic tool. 36 Another potential diagnostic challenge for clinicians managing these patients is the degree to which clinical features of anti-NMDArE and neuroleptic malignant syndrome (NMS) can overlap.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency of normal findings using standard MRI sequences was also indicated in a systematic review of the literature that included 1,167 patients, showing that 62% had normal MRI. Moreover, among the 38% of patients with abnormal findings, the subcortical white matter was as frequently involved as the gray matter . In contrast, when a cohort of 24 patients was examined using MRI DTI sequences, all patients had widespread changes in white matter integrity that correlated with disease severity.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of abnormal MRI findings in cases of anti-NMDAR varies from 11% to 83% [18,46]. Indeed, a systematic review of 56 clinical studies showed that less than 50% of patients had abnormal MRI findings [47], with most abnormalities coming from T2-weighted scans as well as a high FLAIR signal. Abnormal findings are most commonly found in the temporal lobe, in addition to the cerebral cortex and subcortical white matter regions.…”
Section: Imagingmentioning
confidence: 99%
“…Compared with lower-sensitivity MRI, FDG-PET is extremely sensitive for detecting the most severe stages of anti-NMDAR encephalitis [47,51]. Typically, anti-NMDAR encephalitis is characterized by hyperfrontal and temporal lobe metabolism and a decrease in parietal and occipital lobe metabolism.…”
Section: Imagingmentioning
confidence: 99%